PENINGKATAN INTERAKSI SOSIAL DENGAN PEMBERIAN STIMULASI BERMAIN SOSIALISASI PADA MURID SDLBN/C1 (IMBESIL SEDANG) USIA SEKOLAH (6 – 12 TAHUN) DI KABUPATEN TUBAN JAWA TIMUR - NOVIA DWI ASTUTI, NOVIA DWI ASTUTI (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Mild Mental Retardation (C1/Mild Imbesil) with IQ 35 ? 50 has disorder in social interaction so it is needed to stimulation to minimize that disorder. Social interaction namely social and communication contact for the student in SDLBN Tuban with category C1 shows 90% has difficulty. Stimulation playing likes snakeladder has aim to role play to show social and communication contact.            The desain of the research is Eksperimen with Pre Experiment (One group pra-test post-test). The population is the student of SDLBN/C1 (mild Imbesil) age (6-12 years old) in Tuban regency amount 21 students become all sample population. The taking method of sample is simple random sampling, gotten treatment group amount 10 children and control group amount 11 children. Data analize using wilxocon test with Statistical Packages for Social Science (SPSS) for windows 12.0 versionwith strength degree a = 0,05.            Before doing the research gotten 50% respondent have severe and medium social damage interaction in trestment group and control group. After giving game stimulation snakeladder is 62,5% have medium social damage interaction and even there are several show mild and normal social damage interaction. By wilcoxon test and degree of trust 0,05% is gotten significant amount 0,011, it?s means result <0,05% so Ho is rejected.Necessary to have team work between teacher and parents in evaluating child development level and more game modification especially for increasing social personal, soft motoric and language. Not only play snakeladder but also need to increase social interaction stimulation through halma game, monopoli and role play. Key word : mental retardation, imbesil, social interaction, stimulation, snakeladder